(untitled) (Journal of Economic Research & Business Administration, 2016)
This article discusses the development of the hospitality industry today and its current level of development. Prospects of development of hotel business in Kazakhstan are related primarily to the development of tourism. As previously mentioned, tourism generates more revenue for the country receiving it, and this determines the prospects of its development. It provides the basic tourism occupancy and demand for hotels. And also consider the useful side of this sphere of activity to reduce the risk of a world economic crisis. In the course of analyzing considered several favorable factors for the development of this business. More precisely, we analyze appropriateness attendance foreign tourists – places in hotels for the Republic of Kazakhstan, as well as analyzes of the appropriate place in the attendance of the previous year. As a result, we do not consider the developed side of the hotel industry and its low level of maintenance. And we offer a few suggestions for the solution of problems arise when analyzing and achieve the goal of the hospitality industry.